“Radical Enlightenment” – Peripheral, Substantial, or the Main Face of the Trans-Atlantic Enlightenment (1650-1850) (Diametros, 2014)
“Radical Enlightenment” and “moderate Enlightenment” are general categories which, it has become evident in recent decades, are unavoidable and essential for any valid discussion of the Enlightenment broadly conceived (1650-1850) and of the revolutionary era (1775-1848). Any discussion of the Enlightenment or revolutions that does not revolve around these general categories, first introduced in Germany in the 1920s and taken up in the United States since the 1970s, cannot have any validity or depth either historically or philosophically. “Radical Enlightenment” was neither peripheral to the Enlightenment as a whole, nor dominant, but rather the “other side of the coin” an inherent and absolute opposite, always present and always basic to the Enlightenment as a whole. Several different constructions of “Radical Enlightenment” have been proposed by the main innovators on the topic – Leo Strauss, Henry May, Günter Mühlpfordt, Margaret Jacob, Gianni Paganini, Martin Mulsow, and Jonathan Israel – but, it is argued here, the most essential element in the definition is the coupling, or linkage, of philosophical rejection of religious authority (and secularism - the elimination of theology from law, institutions, education and public affairs) with theoretical advocacy of democracy and basic human rights.